Effect of pruning intensity on fruit yield and quality of guava (Psidium guajava L.) cv. Sardar (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted on fifteen-year-old guava (Psidium guajava L) plants of cultivar 'Sardar' planted at 6.5 m x 6.5m at Punjab Agricultural University, Regional Station, Bathinda (Punjab), India. The pruning of plants was done in the first week of March, 2004 with three pruning intensities/levels viz. 15 cm, 30 cm and 45 cm from the shoot tips leaving the unpruned trees as a control. The fruit yield and quality characters were recorded for both rainy season (RS) and winter season (WS) crops. It was observed that the fruit set was significantly higher in pruned trees at 30cm and 45 cm levels as compared to unpruned and lightly pruned trees in WS crop. The maximum number of fruits (430 and 496) and yield (72.2 and 82.3 kg) per tree were recorded in the plants pruned at 15cm level followed by unpruned trees in both WS and RS crops respectively. In both crops, the size of fruits was maximum in trees pruned at 45 cm level followed by 15 cm level and minimum in unpruned trees. An ascending trend of fruit weight with increase in pruning intensity was observed i.e. the weight of fruits was recorded approximately 30 percent more (168.0, 168.1, 170.2g and 168.4, 169.8, 172.3g at 15, 30, 45cm pruning intensities for both RS and WS crops respectively as compared to unpruned (130.4 (RS) and 127.2g (WS)} guava trees. Total Soluble Solids (TSS) percentage was comparatively more (ranging between 10.4 to 11.1 and 10.8 to 11.5 in RS and WS crop, respectively) in the fruits of pruned trees and was least (9.7 and 10.2 in RS and WS crop, respectively) in unpruned trees. Although, acidity in fruits taken from all the pruned trees was at par but higher than the fruits from unpruned trees. The number of seeds in fruits of pruned trees at 15 cm level was significantly higher than fruits obtained from other pruned trees. On the basis of the present study it may be concluded that guava plants respond positively to lighter pruning intensities.
Keywords: Guava pruning; quality; yield